Myocardial infarction with non-obstructive coronary arteries in hypertrophic cardiomyopathy vs Fabry disease. (15th December 2022) - Graziani, Francesca; Lillo, Rosa; Biagini, Elena; Limongelli, Giuseppe; Autore, Camillo; Pieroni, Maurizio; Lanzillo, Chiara; Calò, Leonardo; Musumeci, Maria Beatrice; Ingrasciotta, Gessica; Minnucci, Matteo; Ditaranto, Raffaello; et al.
Abstract: Background: Little is known about prevalence and predictors of myocardial infarction with non-obstructive coronary arteries (MINOCA) in Fabry disease (FD) and hypertrophic cardiomyopathy (HCM). We assessed and compared the prevalence and predictors of MINOCA in a large cohort of HCM and FD patients. Methods: In this multicenter, retrospective study we enrolled 2870 adult patients with HCM and 267 with FD. The only exclusion criterion was documented obstructive coronary artery disease. MINOCA was defined according to guidelines. For each patient we collected clinical, ECG and echocardiographic data recorded at initial evaluation. Results: Overall, 36 patients had MINOCA during a follow-up period of 4.5 ± 11.2 years. MINOCA occurred in 16 patients with HCM (0.5%) and 20 patients with FD (7.5%; p  < 0.001). The difference between the 2 groups was highly significant, also after adjustment for the main clinical, ECG and echocardiographic variables (OR 6.12; 95%CI 2.80–13.3; p  < 0.001). In the FD population MINOCA occurred in 17 out of 96 patients with left ventricle hypertrophy (LVH, 17.7%) and in 3 out of 171 patients without LVH (1.7%; OR 12.0; 95%CI 3.43–42.3; p  < 0.001). At multivariable analysis, voltage criteria for LVH at ECG (OR 7.3; 95%CI 1.93–27.7; p  = 0.003) and maximal LV wall thickness at echocardiography (OR 1.15; 95%CI 1.05–1.27; p  = 0.002) maintained an independent association with MINOCA. No major significant differences were found in clinical, ECG and echocardiographic findings between HCM patients with or without MINOCA. Conclusions: MINOCA was rare in HCM patients, and 6-fold more frequent in FD patients. MINOCA may be considered a red flag for FD and aid in the differential diagnosis from HCM. Highlights: MINOCA is 6-fold more frequent in Fabry Disease vs Hypertrophic Cardiomyopathy. MINOCA may be considered a red flag for Fabry Disease. In Fabry Disease, MINOCA is associated to a more advanced stage of cardiomyopathy.